Translucent optical networks the way forward. - Gangxiang Shen; Tucker, Rodney S.
The transmission reach of signals in optical transmission systems is limited. To go beyond these transparent reach limits, signal regeneration is necessary to re-amplify, reshape, and retime the optical signals. Translucent optical networks are a type of optical transport network specifically devised to address such a concern by allowing for sparse but strategic signal regeneration in the network. Translucent optical networks seek a graceful balance between network design cost and service provisioning performance, and can achieve performance comparable to that of an all-electronic switching network, but requiring far fewer signal regenerators. Despite massive progress, there are many outstanding issues regarding the implementation of translucent networks planning and operation. This article reviews a range of translucent optical networks and discusses various research issues, particularly involving network planning, lightpath routing and wavelength assignment, and network survivability. We also suggest other potential research topics such as traffic grooming, fault detection, and multicasting for translucent networks.
Keywords: Fault detection; Lightpath routing; Network design cost; Network survivability; Optical transmission systems; Optical transport network; Service provisioning performance; Signal regeneration; Traffic grooming; Translucent network multicasting; Translucent network planning; Translucent optical networks; Transparent reach limits; Wavelength assignment